Vulnerability to Psychosis: A Psychoanalytical Perspective. The Paradigmatic Example of 22q11.2 Microdeletion Syndrome - Potier, Rémy; Troubé, Sarah; Putois, Olivier (Frontiers in Psychology, 2020)
This paper outlines a psychoanalytic contribution to a growing research field in psychiatry: that of psychotic vulnerability, and the related neurogenetic modeling of schizophrenia. We explore this contribution by focusing on recent studies concerning a neurodevelopmental disorder, the 22q11.2 microdeletion syndrome – which comprises DiGeorge syndrome in particular. It is one of the most common rare genetic syndromes, and the patients that it affects present a very high rate of psychotic symptoms (between 30 and 40%). For this reason, it has sparked an increasing number of clinical research projects which give it a paradigmatic status, as much for psychotic vulnerability as for potential neurobiological and genetic markers of schizophrenia. This syndrome illustrates one of the major stakes in contemporary psychopathology: the articulation of clinical, neurocognitive, and genetic approaches in a pluri-disciplinary manner. We seek to show that psychoanalysis, when it participates in this articulation, opens up specific hypotheses and research perspectives. In particular, based on the epidemiological observation of the role of anxiety as a predictor for psychosis, we underline the potential relevance of psychoanalytically oriented differential clinical practice and the psychodynamics of anxiety: they can contribute to studies and clinical follow-up on the 22q11.2 microdeletion syndrome and, more widely, to research on the detection and prevention of psychotic vulnerability.